Analysing the glass ceiling and sticky floor effects in Bangladesh: Evidence, Eetent and elements - Faruk, Avinno (Springer Link, 2022)
This article was published in The SN Business & Economics and the definite version is available at: https://doi.org/10.1007/s43546-021-00123-z The Article's website is at: https://link.springer.com/article/10.1007/s43546-021-00123-z